Morphometric evaluation and comparison of soft palate in individuals with and without oral submucous fibrosis: A digital cephalometric study - Radha Anil Deshmukh; Anjana Satish Bagewadi (Wolters Kluwer Medknow Publications, 2015)
Objectives: Oral submucous fibrosis (OSMF) is one of the most common premalignant conditions affecting the oral cavity of people consuming arecanut and gutka. According to the available literature, as the disease progresses the morphology of the soft palate changes. So, the objective of present study was to evaluate and compare the morphology of soft palate in individuals with and without OSMF, using digital lateral cephalogram. Materials and Methods: Sixty male individuals were selected and divided into three groups, Group I-20 individuals (habit group), Group II-20 individuals (OSMF group), and Group III-20 individuals (individuals with no habit and/or OSMF group). The morphology of soft palate was assessed using digital lateral cephalogram. Statistical analysis was carried out using Scheffe multiple comparison test. Results: The superoinferior dimension of soft palate was increased with statistically significant difference in the habit and OSMF groups. The anteroposterior dimension was reduced in the habit group as compared to normal individuals, with statistically significant difference in the OSMF group. The type of soft palate more common in normal individuals and habit group was type 1 and 2, while type 6 was seen more commonly in OSMF group. Conclusion: Cephalometry can be efficiently used to assess the morphology of soft palate and the morphology of soft palate is altered in individuals with the habit even before the development of OSMF. So, cephalometry can be beneficial in assessing fibrosis in individuals with the habit at an early stage, which can further help in prognosis.